Defasagem do Imposto de Renda de Pessoa Física em comparação com a inflação no Brasil - Frana, Virginia (2022)
Currently, a significant portion of the Brazilian population is required to declare personal income tax. The present work has the objective of analyzing and demonstrating calculations of how the income tax table would look, if there were an update in the law. The methodology used was data collection and analysis, using a mixture of two types of research: qualitative and quantitative. Bills nº 4452/2020, nº 2337/2021 and nº 1198/2022 are used, which are being processed in the Federal Senate, and simulations were carried out of what would be the tax due from the taxpayer compared to the current scenario. As the project demonstrates, taxpayers with low income receive a greater discount compared to taxpayers who receive a higher salary, and at the end of the research it is verified that a tax reform is necessary, bringing benefit to the majority, who will have their tax reduced, or even fitting into the exemption range.